A Comprehensive Study of the Analysis of Figurative Language in Alex Haley’s ’’ Roots’’ - Dhain, Ahmed Yasir (International Journal of Psychosocial Rehabilitation, 2020)
This study is distinctively restricted to the analysis of the figurative language that is very important in any literary text and it distinguishes a writer from the others and clothes him with high degree of identity. The study aims to analyze the manner in which style is used in Alex Haley’s Novel Roots. The analysis was intended to investigate some significant rhetorical devices such as (metaphor, symbol, and simile) in Haley’s Roots, and to show how these figures of speech enable Haley to convey his message to the readers. It is divided into eight sections, each analyzing a topic. Finally , the study has reached some conclusions that verify the hypothesis of the study.